Assessment of job satisfaction and contributing factors among community health officers in Chhattisgarh, India - Mandal, Arti Prabha; Agrawal, Bhawna (International Journal Of Community Medicine And Public Health, 2025)
Background: Job satisfaction plays a crucial role in the performance, motivation, and retention of healthcare professionals. Community health officers (CHOs), introduced under the Ayushman Bharat initiative, are pivotal in delivering primary healthcare services at health and wellness centers (HWCs). This study assesses the job satisfaction of CHOs working in the HWCs-sub-health centers (HWC-SHCs) of Chhattisgarh, exploring the key factors affecting their motivation and retention. Methods: A mixed-methods approach was employed. The quantitative component included 100 CHOs from Raipur (non-tribal) and Bijapur (tribal) districts, using a five-point Likert scale for job satisfaction assessment. For the qualitative component, 16 in-depth interviews were conducted to explore personal experiences, challenges, and motivating factors. Data were analyzed using SPSS v.22 and thematic analysis. Results: A total of 61% of CHOs reported dissatisfaction with their jobs, with the most dissatisfaction in monetary benefits (89%). Factors like workload, lack of safety, and management challenges contributed to dissatisfaction. However, CHOs were most satisfied with self-appraisal (80%) and their relationships with coworkers (74%). Bijapur district reported higher satisfaction (56.5%) compared to Raipur (33.8%). Conclusions: The study highlights the need for improved salaries, better safety measures, and workload reduction to enhance CHO job satisfaction. Policy changes addressing these issues are essential for sustainable healthcare delivery in both tribal and non-tribal areas.